(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Objective: The objective of this study is to analyze the adverse drug reactions (ADRs) in hospitalised patients in a tertiary care teachinghospital.Methods: After obtaining institutional ethics committee approval, a cross-sectional study on ADRs reported at the hospital fromOctober 2021 to February 2022 was carried out.Results: There were 45 hospitalizations as a result of adverse drug reactions. Out of these, 28 (62.22%) were women and 17 (37.7%)were men. The majority of cases (62.5%) were moderate in terms of response intensity. Only one patient's estimate of causality (2.5%)was determined to be certain, placing 62.5% of instances in the likely group.Conclusion: This study was carried out to educate practising doctors on the need of monitoring and reporting adverse Drug Reactions.